SIGNIFICANT FACTORS OF THE RIGHT TO DEFEND THE DEFENDANT IN INTERNATIONAL LAW (Heritage, 2021)
In international and national legal theory, basic human rights are defined due to their universal and individual significance. The right to defend the accused is one of them. Given that in legal, political, security theory, the content in question is substantively and precisely elaborated in almost all important documents of international character. The defendant's procedural guarantees were proclaimed in international documents, both of a universal and regional character. The right to defense (as a complex set of rights and duties) can define the procedural position of the defendant. The paper will deal with only some important factors of international standards of the right to defense.
Keywords: human rights, defendant, right to defense.